Innate Lymphocytes in Inflammatory Arthritis - Wu, Xunyao (Frontiers in Immunology, 2020)
Inflammatory arthritis (IA) refers to a group of chronic diseases, including rheumatoid arthritis (RA), psoriatic arthritis (PsA), ankylosing spondylitis (AS) and other spondyloarthritis (SpA). IA is characterized by autoimmune-mediated joint inflammation and is associated with inflammatory cytokine networks. Innate lymphocytes, including innate-like lymphocytes (ILLs) expressing T or B cell receptors and innate lymphoid cells (ILCs), play important roles in the initiation of host immune responses against self-antigens and rapidly produce large amounts of cytokines upon stimulation. TNF (Tumor Necrosis Factor)-IFN (Interferon)-Granzyme B, Th2-related cytokines (IL-4, IL-9, IL-10, and IL-13), IL-17A, IL-22 and GM-CSF are involved in IA and are secreted by ILLs and ILCs. In this review, we focus on the current knowledge of ILL and ILC phenotypes, cytokine production and functions in IA. A better understanding of the roles of ILLs and ILCs in IA initiation and development will ultimately provide insights into developing effective strategies for the clinical treatment of IA patients.